2017
DOI: 10.3390/ijms18081636
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Perspective on the ApoM-S1P Axis, Highlighting the Metabolism of ApoM and Its Role in Liver Fibrosis and Neuroinflammation

Abstract: Hepatocytes, renal proximal tubule cells as well as the highly specialized endothelium of the blood brain barrier (BBB) express and secrete apolipoprotein M (apoM). ApoM is a typical lipocalin containing a hydrophobic binding pocket predominantly carrying Sphingosine-1-Phosphate (S1P). The small signaling molecule S1P is associated with several physiological as well as pathological pathways whereas the role of apoM is less explored. Hepatic apoM acts as a chaperone to transport S1P through the circulation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 148 publications
0
20
0
Order By: Relevance
“…We compared the expression of proangiogenic factors, which was upregulated by albumin-bound S1P stimulation as described above, in the presence of 1 μM ApoM with albumin-bound S1P. ApoM is a member of the Lipocalin family, which has a calyx-like pocket binding to S1P [ 37 ]. ApoM is secreted by hepatocytes and stored in the blood plasma.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We compared the expression of proangiogenic factors, which was upregulated by albumin-bound S1P stimulation as described above, in the presence of 1 μM ApoM with albumin-bound S1P. ApoM is a member of the Lipocalin family, which has a calyx-like pocket binding to S1P [ 37 ]. ApoM is secreted by hepatocytes and stored in the blood plasma.…”
Section: Resultsmentioning
confidence: 99%
“…Several reports have suggested different mechanisms between ApoM-bound S1P and albumin-bound S1P [ 37 ]. Ruiz et al demonstrated that ApoM-bound S1P restrained the TNF-α-induced expression of adhesion molecules (E-selectin, intercellular adhesion molecule-1, and vascular adhesion molecule-1) in primary human aortic endothelial cells (HAECs) [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…A published study showed significantly reduced sphinogsine-1P levels in the plasma of older Tangier subjects with very low levels of HDL and apoAI (99% and 97% reduction, respectively) (43). It is known that sphinogsine-1P transport to plasma involves apoM and spinster 2 and resides mainly on HDL 3 (6,(44)(45)(46). Longitudinal, prospective studies in larger cohorts are needed to determine plasma apoM, sphingoid bases, and their phosphate levels in Tangier subjects.…”
Section: Sphingoid Bases and Their Phosphatesmentioning
confidence: 99%
“…Plasma apoM mainly associates with high-density lipoproteins (HDL) (more than 90%) and to a minor extent with low-density lipoproteins, very low-density lipoproteins, and chylomicrons [ 23 ]. HDL-associated apoM carries about 65% of plasma S1P, whereas albumin is able to transport approximately 30% of S1P [ 24 ]. As hepatocytes express and secrete the majority of circulating apoM, the liver plays a crucial role in maintaining the S1P gradient between blood and lymphoid tissues.…”
Section: Regulation Of Plasma S1p Content Via Liver-formed Apolipomentioning
confidence: 99%